Electronic Structure, Spectroscopic (IR, Raman, UV-Vis, NMR), Optoelectronic, and NLO Properties Investigations of Rubescin E (C31H36O7) Molecule in Gas Phase and Chloroform Solution Using Ab Initio and DFT Methods - Richard Arnaud Yossa Kamsi; Geh Wilson Ejuh; Fidèle Tchoffo; Pierre Mkounga; Jean-Marie Bienvenu Ndjaka (Advances in Condensed Matter Physics)
Quantum chemical methods were used to study the electronic structure and some physicochemical properties of Rubescin E molecule. Good agreement with experiment was found for J3H-H coupling constant, IR, 1H NMR, and 13C NMR. The excitation energy and oscillator strength calculated by TD-DFT also complement with experiment. Large values were obtained for dipole moment, polarizability, first static hyperpolarizability, electric susceptibility, refractive index, and dielectric constant, meaning that Rubescin E has strong optical and phonon application and can be a good candidate as NLOs material. The 3D analysis of the title molecule leads us to the conclusion that electron can easily be transferred from furan to tetrahydrofuran ring. The global reactivity descriptors were evaluated. Mulliken, ESP, and NBO charges comparisons were carried out and described.